Effects of consumption of cow's milk by the child before the first year of life (Research, Society and Development, 2022)
Introduction: Infant feeding is an essential factor for the full growth and development of the child. Objective: to analyze the effects of the introduction of cow's milk on the child's diet before one year of life. Materials and Methods: This is an integrative review of the literature, developed from research in lilacs, MEDLINE, PubMed, virtual health library and Scielo, from the descriptors: breastfeeding, early weaning, cow's milk and exclusive breastfeeding. Inclusion criteria were studies addressing factors related to infant feeding and the effects of early weaning and the insertion of cow's milk in the health and adequate development of children under one year of age, articles written in Portuguese, published from 2008 to 2021, available electronically. Final considerations: Cow's milk is not the most recommended for feeding the child before a year of life, because in addition to not meeting the nutritional needs of the child can trigger allergies and food intolerances, chronic diseases such as obesity and diabetes mellitus and iron deficiency anemia.